EFFORTS TO INCREASE TEACHER TEACHING SKILLS IN APPLYING PROBLEM BASED LEARNING MODELS THROUGH GROUP GUIDANCE - Sukarman Sukarman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The task and role of the teacher are not only teaching but developing learning tools and evaluating student learning. This study aims to improve teacher teaching skills in applying problem-based learning models through group guidance. This type of research is school action research. This study was conducted on SDN 001 teachers with a total of 19 teachers, researching from September to October 2019. Data obtained from observation sheets that observe the actions of teachers and student activities during learning takes place. The results showed that the teaching skills of teachers in the first cycle gained an average percentage of 61% with a category that experienced an increase in cycle II with an average percentage achievement of 72% which was included in the good category. Conclusion of this study that the teaching skills of SDN 001 Petai in applying the problem-based learning model had increased through group guidance.